Guide to Cebu's world of higher education all about Cebu's universities, colleges and others institutions of higher learning - Barreveld, Dirk J. (Mandaue City, Cebu Arcilla Travel Guides, 2000)
It provides a comprehensive list of universities and colleges in Cebu. It also has information that can help foreign students deal with studying in Cebu.
Keywords: Universities and colleges -- Philippines -- Cebu -- Directories